Stauropathes Opresko 2002 - Lima, Manuela M.; Cordeiro, Ralf T. S.; Perez, Carlos D. (Zenodo, 2019)
Genus Stauropathes Opresko, 2002 Type-species. Stauropathes staurocrada Opresko, 2002 (by original designation). Diagnosis. “Corallum sparsely to densely branched. Stem and branches pinnulate. Pinnules simple, bilateral in two rows, and subopposite. Spines triangular and compressed. Polyps usually 3–6 mm in transverse diameter” (Opresko, 2002). Remarks. The genus Stauropathes Opresko, 2002 groups three species: S. staurocrada Opresko, 2002, S. arctica (Lütken, 1872) and S. punctata (Roule, 1905). As the specific epithet itself already suggests, S. arctica occurs only in the Arctic Ocean, with its southern latitudinal limit of 58 ° N, with a bathymetric range of 461 to 1700 m. S. staurocrada has an extensive distribution in the Pacific Ocean, occurring on the coast of New Zealand, Hawaii, and other points to the north (Mid Pacific Mountains), at depths of 54 to 1700 m. Stauropathes punctata occurs in the North Atlantic, Azores and Cape Verde, in a bathymetric range of 1300 to 2000 m (Opresko, 2002; Molodtsova, 2006). Distribution. Arctic, Atlantic and Pacific (Opresko, 2002). Published as part of Lima, Manuela M., Cordeiro, Ralf T. S. & Perez, Carlos D., 2019, Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic, pp. 1-67 in Zootaxa 4692 (1) on pages 40-41, DOI:10.11646/zootaxa.4692.1.1, http://zenodo.org/record/3528942